The Inventory Control, Storage Facilities and Distribution at Pharmaceutical Industry in Supporting Drugs Availability of JKN Era - Satibi Satibi; Achmad Fudholi; Eirene Copalcanty Tuko; Gabriela Larasati Swastiandari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The drugs availability is still a problem in the health system in Indonesia. The number of JKN participants increasing the need for generic drugs. Pharmaceutical industry has a role to produce affordable and good quality medicines by implementing good supply chain. The purpose of this study was to identify the role of inventory control, storage and distribution facilities in the pharmaceutical industry in supporting drugs availability in the JKN era. This is a descriptive research with qualitative method and uses purposive sampling. Data was collected in depth interview with employees from the PPIC and SCM in Pharma A, Pharma B, Pharma C and Pharma D that collaborated with BPJS Kesehatan and become drug providers in e-catalogue tender. Data analysis consisted of making interview transcripts, interpreting data, and triangulation. The results of the analysis showed that inventory control has an influence in the pharmaceutical industry in supporting the drugs availability due to a mismatch between demand and need, thereby increasing the occurrence of stock over or stock out. Facilities of storage has an influence in the pharmaceutical industry in supporting the drugs availability due to overload storage facilities so that the storage method was not optimal and has to pay other costs to rent warehouses. Distribution has an influence in the pharmaceutical industry in supporting the drugs availability because the costs for distribution must reach a minimum order to be distributed and the choice of transportation modes for distribution may be increased the lead time that caused the drug vacancies.